THE ENHANCEMENT OF CLASSIFICATION AND PREDICTION SKILLS IN BUFFER AND HYDROLYSIS LESSON BY PROBLEM SOLVING LEARNING MODEL - tri aulia mutia; ratu betta rudibyani; chansyanah diawati (Jurnal Pendidikan dan Pembelajaran Kimia, 2012)
This research was conducted to describe the effectiveness of the learning model of problem solving in improving classification and prediction skills. This research used a quasi experimental method with One Group Pretest-Posttest Design.  Subjects in this research were students of SMAN 1 Bandar Sribhawono Even semester of classes XI IPA1 and classes XI IPA2 School Year 2011-2012.  The effectiveness of the learning model of problem solving was measured by differences in understanding of the beginning and end of the students understanding shown by the mean N-gain between control and experimental classes.  Statistic analysis is used of this research is average two differences test with uji-t.  Based on the results of this research, average value of N-gain for classification skills of control and experimental classes is 0.53 and 0.70; and the average value of N-gain for prediction skills of control and experimental classes is 0.53 and0.63. Based on the results of this hypothesis test, known that classes with problem solving learning had classification and prediction skills more higher than classes with convensional learning.  This shows that a model of problem solving is effective in improving the classification and prediction skills students of SMAN 1 Bandar Sribhawono.Keywords: Problem Solving, classification skill and prediction skill